What’s in a Sámi Proverb? Linguistic Remarks about Sámi Proverbs - Gibert, Guillaume (Sámi dieđalaš áigečála, 2025)
The aim of this paper is to investigate the linguistic features of Sámi proverbs and to show how these special statements work. Based on Harald Gaski’s Jođi lea buoret go oru: Time is a Ship That Never Casts Anchor collection of proverbs, the article is the first to shed light on certain syntactic, semantic, and pragmatic properties of Sámi proverbs. Furthermore it is shown that accentual and metrical patterns can be found in proverbs, which, in addition to similar linguistical features, makes it possible to compare proverbs and poetic texts, both in ancient and contemporary poetry. The article concludes by commenting on the fuzzy boundaries between literary genres and the liveliness of proverbs in Sámi culture.